New Media, Legacy Media and Misperceptions Regarding Sourcing - Stan Diel (KOME: An International Journal of Pure Communication Inquiry, 2017)
Resource dependence theory and related theories of management suggest online-only news media may displace legacy news media, but until that happens the two systems are likely to be dependent on the same resource: news. This quantitative content analysis finds that the systems exist as parallel but distinctly separate entities. Websites associated with legacy news media such as newspapers publish mostly hard news or news analysis in the form of original work. New, online-only news media publish mostly unoriginal features, but the origins of much of the content published by onlineonly media are unclear.